Bloodstream infections in hospitalized patients before and during the COVID-19 surge in a community hospital in the South Bronx. (March 2022) - Afzal, Afsheen; Gutierrez, Victor Perez; Gomez, Edgar; Mon, Aye Myat; Sarmiento, Carolina Moreira; Khalid, Amna; Polishchuk, Svetlana; Al-Khateeb, Mohannad; Yankulova, Boyana; Yusuf, Mubarak; de Castro, Yinelka Silverio; Pillai, Anjana; et al.
Highlights: Higher incidence of bloodstream infections (BSI) among patients during the COVID-19 surge. Increased hospital-acquired and central line-associated BSI during the COVID-19 surge. Enterococcus spp. was the most common microbe causing BSI during the COVID-19 surge.